Pengaruh Pupuk Kompos Ampas Tahu Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Pagoda (Brassica Narinosa L.) - Isnaeni Opnamiati; Nurlaila Fatmawati (Journal of Horticulture Production Technology, 2026)
This study aimed to evaluate the effect of tofu dregs compost on the growth and yield of pagoda mustard (Brassica narinosa L.). The experiment was conducted from February to May 2025 in Beji, Banjarmangu, Banjarnegara, Indonesia, using a non-factorial Randomized Complete Block Design (RCBD) with five treatments and nine replications. Data were analyzed using analysis of variance (ANOVA), followed by the Honest Significant Difference (HSD) test at the 5% significance level. The results showed that tofu dregs compost significantly affected all measured growth and yield parameters of pagoda mustard. The application of 200 g of compost per plant produced the highest values for plant height (16.92 cm), number of leaves (19.06 leaves), leaf area (101.56 cm²), fresh weight (31.74 g), and dry weight (11.20 g), and these values were significantly higher than those obtained with the other treatments. The improved plant performance suggests that an adequate supply of organic matter and nutrients from tofu dregs compost promoted vegetative growth and biomass accumulation. Therefore, the application of 200 g of tofu dregs compost per plant can be recommended as an effective practice for enhancing the growth and yield of pagoda mustard.